Morphological description and DNA barcoding of Hydrobaenus golovinensis sp. nov. (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East - Makarchenko, Eugenyi A.; Makarchenko, Marina A.; Semenchenko, Alexander A.; Veliaev, Oleg A. (Zootaxa, 2017)
Illustrated descriptions of adult male, pupa and fourth instar larva, as well as DNA barcoding results of Hydrobaenus golovinensis sp. nov. in comparison with closely related species H. majus Makarchenko et Makarchenko and H. sikhotealinensis Makarchenko et Makarchenko from the Russian Far East are provided. Partial mitochondrial COI gene (DNA barcoding) of the new species has been sequenced and uploaded to GenBank. Comparisons with corresponding regions of COI between H. golovinensis and other species in the genus produce K2P genetic distances of 10.3–14.3%, the values well above those associated with intraspecific variation. In contrast, genetic distances among 18 specimens are all within the range of 0–3.5%. The ML tree is also constructed using DNA barcodes obtained in the present study and those of other species of Hydrobaenus Fries from GenBank.